The principle of the power of will and its effect in the commercial lease contract - Badache, Saad (Journal of Human Sciences, 2022)
The contract’s principal is when the parties are being free to establish and arrange the effects, by taking in to account the following public order and morals, in addition to some mandatory provisions prescribed by the legislator which regulate the contract, and whether most special rules of a particular contract are initiatively considered as interpretative rules, to be applied if they have not been agreed, by to the contractor thus contrator’s desire is to set up legal conduct, and determine its effects this infact is the principle of the authority’s, whill in which the contract is based on the principal of “ pacta sunt servanda “ legal conduct is determined, by both the will and agreement of the contracting parties, one of the most important contracts that the will has played a crucial role in regulating them, is the contract of the commercial lease that we are considering , However this has not prevented the legislator from interfering the legislator, may interfere by establishing legal controls, in order to provide legal protection to both the lessor and the less.